GRANODIORITES OF OLEKMINSKY COMPLEX OF THE EASTERN TRANSBAIKALIA: U-Pb LA-ICP-MS ZIRCONS GEOCHRONOLOGY AND AGE POSITION OF COMPLEX - S. I. Dril; V. P. Kovach; А. В. Kotov; K.-L. Wang; А. М. Larin; Y. Iizuka; H.-Y. Lee (Геодинамика и тектонофизика, 2024)
The palingenic calc-alkaline granitoid massifs of the Olekminsky complex form a magmatic belt stretching within the Western-Stanovoy terrane in the northeastern direction for more than 700 km. New U-Pb LA-ICP-MS dates for zircons from the granodiorites of the Marekta-Bereinsky massif of the Olekminsky complex and the granodiorites of the Yamninsky massif of the Krestovsky complex were obtained, amounting to 371±4 Ma and 364±5 Ma, respectively. These geochronological data are well consistent with the 355–358 Ma ones, therefore suggesting the Late Carboniferous age of quartz-diorite-granodiorite-granite rocks of the Olekminsky complex. However, these dates are not correlated with the existing legends of geological maps covering the area of the Western-Stanovoy structural-formation zone or the Western-Stanovoy terrane, as the intrusive formations of the Olekminsky complex are dated as the Early Paleozoic. In addition, new geochronological data call into question distinguishing of a separate Early Paleozoic Krestovsky granitoid complex.